Characterization of FANCL variants observed in patient cancer cells. Issue 6 (4th June 2020) - Frost, Mark G.; Mazloumi Aboukheili, Amir Mahdi; Toth, Rachel; Walden, Helen
Abstract: Fanconi Anemia (FA) is a rare genetic disorder characterized by developmental defects, bone marrow failure and high predisposition to cancer. The FA DNA repair pathway is required in humans to coordinate repair of DNA interstrand cross-links. The central event in the activation of the pathway is the monoubiquitination of FANCD2 and FANCI by the E2-E3 pair, Ube2T-FANCL, with the central UBC-RWD (URD) domain of FANCL recognizing the substrates. Whole genome sequencing studies of cancer cells from patients identified point mutations in the FANCL URD domain. We analysed 17 such variants of FANCL, including known substrate binding mutants (W212A, W214A and L248A, F252A, L254A, I265A), a FA mutation (R221C) and 14 cancer-associated mutations (F110S, I136V, L149V, L154S, A192G, E215Q, E217K, R221W, T224K, M247V, F252L, N270K, V287G, E289Q) through recombinant expression analysis, thermal shift assay, interaction with FANCD2, in vitro ubiquitination activity, and cellular sensitivity to an interstrand cross-linking agent. We find that the FANCL mutations I136V, L154S, W212A and L214A, R221W, R221C, and V287G are destabilizing, with N270K and E289Q destabilizing the C-terminal helices of the URD domain. The hydrophobic patch mutant (L248A, F252A, L254A, I265A), along with mutations E217K, T224K, and M247V, cause defects in the catalytic function of FANCL. This highlights the C-terminal lobe of the FANCL URD domain as important for the activity and function of FANCL. These mutations which affect the fold and activity of FANCL may contribute to tumorigenesis in these non-FA cancer patients, and this implicates FA genes in general cancer progression.